Primary endoscopic drainage of an infected renal cyst via a preexisting duodenal fistula - Massad Mutaz (22504358) (2024)
Renal cyst – duodenal fistula is not common and we know little about their presentation and management. The present case report describes a unique endoscopic technique to manage an infected renal cyst through a preexisting duodenal fistula. A retrospective evaluation and analysis were performed of a patient with an infected renal cyst‐duodenal fistula seen in our unit. Patient symptoms, imaging findings, and details of endoscopic procedures were evaluated. The Need for minimally invasive techniques is increasing nowadays as both diagnostic and therapeutic approaches. One of these modalities is the endoscopic management of gastrointestinal fistulae. Minimally invasive techniques can be used as a bridge to major surgeries in those who are not candidates initially. Other Information Published in: International Journal of Urological Nursing License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/ijun.12417